Family and Child Themed Poems in Modern Arab Literature - YÜKSEK, Ayşe (Scientific Journal of Faculty of Theology, 2022)
Every society gives importance to the education of children. It uses various elements for their education. In Classical Arabic Literature, there were poems about family, child and child education. However, such poems are more common in Modern Arabic Children's Literature. Children's Literature puts the child in the focus. It contributes to the mental, psychological, cultural, and social development of children. It develops the national and spiritual feelings of the child. In addition, he makes his contribution to the child's language development with great pleasure. It appeals to the child's sense of aesthetics and pleasure and provides the child with literature knowledge in many fields. There is often an emphasis on family values in this genre of literature. In addition, the content of such poems includes love of parents, love of country, love of environment and animals. Religious feelings, moral values, friendship, and fraternity are also frequently seen there. Thus, it benefits the development of the child in many areas. In this way, it is aimed that the child will be a useful individual for both himself and the society. Children's literature is a type of literature developed in modern societies. While educating the countries and children to the whole world, it presents its own culture, civilization, philosophy, and ideals with different literary elements. Because strong children's literature means a strong society. The pioneers of children's poetry in the modern sense are names such as Muhammed Herrâvî, Rifae et-Tahtavi, Muhammed Osman Celâl, Ahmet Şevki, Abdüttevvâb Yusuf, Süleyman el-Îsâ, Ahmed Necib, Abdürrezzak Ca'fer, Ahmed Süveylem, Ahmed Zerzûr, Zekeriyâ Tâmir are names such as Alî es-Sıkılîand.In this paper, the works written by these poets who pioneered Modern Arabic Literature and the issues related to children and families in their works will be included.